Understanding reading in English: an analysis of students’ project work - Wan Mansor , Wan Fara Adlina (2011)
This study attempts to investigate the students’ understanding of reading in English by analyzing the students’ project work. The objectives are to know the skills in note making the students used to assist in their understanding of reading text and how the note making help them in writing a summary. This study also looks at how the students’ proficiency in English help them in understanding their reading material. Data were taken from the project work made by the students. The project work requires the students to read a piece of reading material, make notes on the reading material and write a summary of the reading material based on the note making that they have made. The students who did the project works were from the TESL and Civil in Education course in Faculty of Education in UTM. The findings show that most of the students employ some type of skills in note making. These skills are; using linear and non-linear form of note making, clear organization of idea, using simple words in the note making and also sufficient content. In addition, the students’ proficiency in English also plays a role in understanding English. This study aims to help the students in their reading of English as a Second language by providing the skills that are useful in note making that can assist in understanding reading in English. It is also hoped that teachers of English as a Second language will benefit from the study where they can use the skills provided in their language learning classroom.